Pembuatan dan Perbaikan Modul Training pada Plant Secondary Processing Departemen Operation Training di PT. X - Yongki Hadi; Debora Anne Yang Aysia (Jurnal Titra, 2014)
PT. X, one of the leading tobacco companies in Indonesia, needs competent and good quality of human resources to achieve their goal. PT. X has an Operation Training Department. This department is responsible to provide trainings for the operators, production technicians (prodtech), and mechanics. Therefore, training modules based on Best Training Practices (BTP) method is needed. There are four training modules that have been developed and three training modules that have been revised on the secondary processing plant. The four modules that have been developed were PACKER F Training Module for Operators, PACKER F Training Module for Prodtechs, PACKER F Training Module for Mechanics and MAKER M Training Module for Mechanics. The three modules that have been revised were Basic Training Module for Mechanics, MAKER P Training Module for Operator, and MAKER P Training Module for Prodtech. The training modules that were constructed will help training processes going well and improve the employees’ performance.